On the Investigation of Microstructured Charcoal as an ANFO Blasting Enhancer - Suzana Gotovac Atlagic; Andrzej Biessikirski; Łukasz Kuterasiński; Michał Dworzak; Michał Twardosz; Niki Sorogas; John Arvanitidis (Energies, 2020)
In this study, we examined the influence of microstructured charcoal (MC) when added to ammonium nitrate fuel oil (ANFO) samples. We performed a study that investigated ANFOs structure, crystallinity, and morphology by utilizing infrared spectroscopy (IR), X-ray diffraction (XRD), and scanning electron microscopy (SEM), respectively. MC characteristics were probed by Raman spectroscopy and SEM analysis. SEM analysis indicated how fuel oil (FO) covered ammonium nitrate prill. Moreover, the surface of the MC was covered by specific microfibers and microtubes. The disordered graphitic structure of the MC was also confirmed by Raman spectroscopy. Simulation of blasting properties revealed that the addition of MC should decrease blasting parameters like heat explosion, detonation pressure, and detonation temperature. However, the obtained differences are negligible in comparison with the regular ANFO. All analyses indicated that MC was a good candidate as an additive to ANFO.